2017
DOI: 10.1016/j.lindif.2017.03.010
|View full text |Cite
|
Sign up to set email alerts
|

The proxy-measurement of intelligence quotients using a relational skills abilities index

Abstract: Relational Frame Theory proposes that levels of sophistication with relational concepts may underlie intellectual performance. In order to further elucidate this relationship, the current study examined correlations between scores on a novel Relational Abilities Index (RAI) and a range of widely-used cognitive ability measures, including Full Scale IQ. In Study 1, 35 adult participants completed a battery of cognitive assessments, comprising of the National Adult Reading Test, the Rey Auditory Verbal Learning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 34 publications
2
12
0
Order By: Relevance
“…Therefore, they can also be trained by manipulating the environment (see Kishita, Ohtsuki, and Stewart (2013); McLoughlin and Stewart (2017); Moran, Walsh, Stewart, McElwee, and Ming (2015)). Not only can relational operants be trained, but they are strongly associated with IQ (Colbert et al, 2017), and this is congruent with converging consensus from the fields of neuroscience (Davis et al, 2017), linguistics (Everaert et al, 2015;Goldwater, 2017), evolutionary biology (Wilson & Hayes, 2018), and cognitive psychology (Alexander, 2019;Goldwater, Don, Krusche, & Livesey, 2018;Goldwater & Schalk, 2016;Halford, Wilson, & Phillips, 2010;Kaufman, DeYoung, Gray, Brown, & Mackintosh, 2009) that relational reasoning is central to cognition.…”
supporting
confidence: 61%
“…Therefore, they can also be trained by manipulating the environment (see Kishita, Ohtsuki, and Stewart (2013); McLoughlin and Stewart (2017); Moran, Walsh, Stewart, McElwee, and Ming (2015)). Not only can relational operants be trained, but they are strongly associated with IQ (Colbert et al, 2017), and this is congruent with converging consensus from the fields of neuroscience (Davis et al, 2017), linguistics (Everaert et al, 2015;Goldwater, 2017), evolutionary biology (Wilson & Hayes, 2018), and cognitive psychology (Alexander, 2019;Goldwater, Don, Krusche, & Livesey, 2018;Goldwater & Schalk, 2016;Halford, Wilson, & Phillips, 2010;Kaufman, DeYoung, Gray, Brown, & Mackintosh, 2009) that relational reasoning is central to cognition.…”
supporting
confidence: 61%
“…A small number of correlational analyses (Colbert et al, 2017;Dixon et al, 2014;O'Hora et al, 2005O'Hora et al, , 2008 have further underlined the relationship between relational responding and intellectual performance by assessing performance on traditional IQ test performance and assessments of relational skills. For instance, across two separate analyses, O'Hora et al (2005) andO'Hora et al (2008) reported significant correlations between performance on a temporal relations task (before/after) and all three WAIS-III indices (Full Scale, Verbal, and Performance IQ), two of four WAIS-III subindices (Verbal Comprehension and Perceptual Organization) and two WAIS-III subtests (Vocabulary and Arithmetic).…”
Section: Relational Ability and Measures Of Intellectual And Academic Abilitymentioning
confidence: 99%
“…The Relational Abilities Index (RAI), initially developed by Cassidy ( 2008) and later extended by Cassidy et al (2016), is in its current form a 55-item syllogistic reasoning assessment that measures proficiency in coordination, opposition, and comparison relational responding, and is now regarded as an acceptable proxy measure of IQ (Colbert et al, 2017). Colbert et al (2017) carried out the most in-depth analysis of the RAI to date, reporting medium to strong correlations between RAI scores and all three WAIS-III indices (Full Scale, Verbal and Performance IQ), all four subscales (Verbal Comprehension, Working Memory, Perceptual Organization and Processing Speed), as well as 10 of 13 IQ subtests. In addition, in the second of the Colbert et al's studies, RAI scores predicted performance on number of other measures of cognitive ability, including verbal ability (National Adult Reading Test; Nelson, 1982), visuospatial function (the Trail Making Test; Lezak, 1995), and memory (Rey Auditory Visual Learning Tests;Rey, 1958;English version: Taylor, 1959).…”
Section: Relational Ability and Measures Of Intellectual And Academic Abilitymentioning
confidence: 99%
See 2 more Smart Citations